MANIFESTATION OF THE ATTENTION PROCESS IN CHILDREN WITH SPEECH IMPAIRMENT (Web of Teachers: Inderscience Research, 2024)
This article discusses the features of the manifestation of the attention process, one of the cognitive processes in children with speech impairments.